Super-resolution imaging of synaptic and Extra-synaptic AMPA receptors with different-sized fluorescent probes - Sang Hak Lee; Chaoyi Jin; En Cai; Pinghua Ge; Yuji Ishitsuka; Kai Wen Teng; Andre A de Thomaz; Duncan Nall; Murat Baday; Okunola Jeyifous; Daniel Demonte; Christopher M Dundas; et al. (eLife, 2017)
Previous studies tracking AMPA receptor (AMPAR) diffusion at synapses observed a large mobile extrasynaptic AMPAR pool. Using super-resolution microscopy, we examined how fluorophore size and photostability affected AMPAR trafficking outside of, and within, post-synaptic densities (PSDs) from rats. Organic fluorescent dyes (≈4 nm), quantum dots, either small (≈10 nm diameter; sQDs) or big (>20 nm; bQDs), were coupled to AMPARs via different-sized linkers. We find that >90% of AMPARs labeled with fluorescent dyes or sQDs were diffusing in confined nanodomains in PSDs, which were stable for 15 min or longer. Less than 10% of sQD-AMPARs were extrasynaptic and highly mobile. In contrast, 5–10% of bQD-AMPARs were in PSDs and 90–95% were extrasynaptic as previously observed. Contrary to the hypothesis that AMPAR entry is limited by the occupancy of open PSD ‘slots’, our findings suggest that AMPARs rapidly enter stable ‘nanodomains’ in PSDs with lifetime >15 min, and do not accumulate in extrasynaptic membranes.